2006
DOI: 10.5301/jbm.2008.5160
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of chromogranin A as a prognostic factor in organ-confined prostate cancer

Abstract: The clinical significance of neuroendocrine differentiation in patients who have undergone surgery for localized prostate cancer is still unclear. The aims of this study were to assess the relationship between serum neuroendocrine markers and well-known prognostic factors in prostate cancer (pathological staging, definitive Gleason score and serum PSA) and to search for correlations between serum chromogranin A (CgA) levels and pathological findings. Forty-one consecutive patients who had undergone radical ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Some report its utility in early diagnosis, particularly when used in conjunction with free/total PSA ratio; 9,10 however, others have found CgA does not accurately distinguish benign from malignant disease. 11 Similar controversy exists between CgA and tumor characteristics, [10][11][12] and CgA does not appear to be prognostic of disease recurrence after radical prostatectomy (RP) or radiation therapy. 13,14 Inconsistencies may be explained by the fact that while most CaPs are characterized by NE differentiation, it is a transient and reversible process and thus NE markers may not always be detectable and a subset may have no NE differentiation.…”
Section: Markers Of Neuroendocrine Differentiationmentioning
confidence: 99%
“…Some report its utility in early diagnosis, particularly when used in conjunction with free/total PSA ratio; 9,10 however, others have found CgA does not accurately distinguish benign from malignant disease. 11 Similar controversy exists between CgA and tumor characteristics, [10][11][12] and CgA does not appear to be prognostic of disease recurrence after radical prostatectomy (RP) or radiation therapy. 13,14 Inconsistencies may be explained by the fact that while most CaPs are characterized by NE differentiation, it is a transient and reversible process and thus NE markers may not always be detectable and a subset may have no NE differentiation.…”
Section: Markers Of Neuroendocrine Differentiationmentioning
confidence: 99%
“…Similarly, Kamiya et al found that the mean NSE serum level in metastatic PCa patients was significantly higher than that in nonmetastatic patients (p<0.05) (21). Conversely, 3 other studies did not find any association between the pretreatment serum levels of NSE and T category (17,18,22).…”
Section: Correlation Between Serum Nse and Stagementioning
confidence: 92%
“…No additional studies were found in screening the references of those selected articles. Finally, 19 articles including 1,772 patients with confirmed or suspicious PCa were selected for the systematic review (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Some indicate CgA utility in early diagnosis, particularly when used in combination with free/total PSA ratio, [26] however, some studies found that CgA does not precisely differentiate malignant disease. [27] Similar debate occurs regarding CgA and tumor features [28] and CgA does not show any advantage in the prognosis of PCa recurrence after radical prostatectomy or radiotherapy. [29] Inconsistencies may be attributed to the transient and reversible process of neuroendocrine differentiation (NED) in most malignant prostate tumors; thus, these NE molecules are not constantly detectable.…”
Section: Introductionmentioning
confidence: 99%